EFFECT OF DIFFERENT PARAMETERS OF THE BIOLOGICAL PROCESSES ON THE SPECIFIC GROWTH RATE OF NITRIFYING BACTERIA BY MEANS OF MATHEMATICAL MODELS - NAJMAN, KAROJ; PANGLISCH, STEFAN; KATAYAMA, VICTOR (Journal of Duhok University, 2021)
In this study, the biological removal of nitrogen from wastewater with relatively high ammonium concentration is investigated by modelling and simulation. Specifically, the nitrification process, means the oxidation of ammonium to nitrate, which is catalysed by two types of bacteria, namely ammonium-oxidising bacteria (AOB) and nitrite-oxidising bacteria (NOB). In wastewater treatment, ammonia oxidation lowers the pH of wastewaters with in relation to total ammonia limited alkalinity. By reducing the pH, ammonia oxidation often stops just below pH 6-6.5. On the other hand, nitrification has been found to occur even at low pH in reactors that process human urine, although it was not clear which species of bacteria are involved. Against this background, this research used different mathematical models of ammonia-oxidising bacteria (AOB). The aim is to estimate those sludge residence times as a function of pH that can achieve complete nitrification of the NH3-N load in the influent. Quantity of base that should be dosed to the system and the capacity of the bioreactor have been calculated using estimated data. The values obtained have also been compared with the values from literature.